Colistin as A Good Monotherapy to Restrain the Pathogenicity of Acinetobacter baumannii In vivo and In vitro (Baghdad Science Journal, 2022)
Acinetobacter baumannii  (A. baumannii) is a major opportunistic nosocomial pathogen, mostly resistant to several groups of antibiotics. Colistin is now used as a last-line treatment for isolates that are highly resistant. The purpose of this study is to identify the importance of LptD; which is involved in the translocation of LPS from the inner membrane to the outer membrane in compartment with LptA and LptC of A. baumannii and its indispensable role as a virulence factor, and the efficiency of colistin as a monotherapy. In the current research, two isolates of A.baumannii were used, the local isolate HHR1 isolated from urine sample and the global strain ATCC 17904, and three antibiotics (colistin, rifampicin and Fosfomycin) were used as a monotherapy and synergic therapy in vivo and ex vivo. The results demonstrated that A. baumannii HHR1 was more resistant to Antimicrobial peptides (AMPs) than the standard strains. The effect of AMPs  on A. baumannii was increased by increasing the concentration and the time of incubation, and also AMPs were shown to be lethal on A. baumannii growth spatially at high concentration (2 µg ml-1) in  monotherapy and (1.5, 2 µg ml-1) in synergic. The susceptibility of isolates towards antibiotics was variable, where colistin exerts significant growth had defect as a monotherapy and in combination with others. The results showed that the expression of lptD, lptA genes of A.baumannii HHR1 were  higher than of  the same genes in A.baumannii ATCC 17904 in the presence of 2 µg ml-1  colistin, while lptE gene of the A.baumannii ATCC 17904 showed an upregulation pattern  than in A.baumannii HHR1. Furthermore, colistin influences the adhesion ability of A. baumannii on epithelial cells (A-549 lung cancer cell) by reducing the number of cells, and thus could colistin be a good candidate for A. baunmannii treatment.